Influence of the soil water holding capacity on the potential distribution of forest species. A case study: the potential distribution of cork oak (Quercus suber L.) in central-western Spain - Jovellar Lacambra, Luis Carlos; Blanco Andray, Alfredo; Santos Francés, Fernando (European Journal of Forest Research, 2008)
This study reports a parametric approach to the climatic and edaphoclimatic potential distribution of the cork oak (Quercus suber L.) in central-western Spain together with an analysis of the in Xuence of the maximum soil water holding capacity (WHC) on such potential distribution. To these ends, we employed 12 climatic and 2 edaphoclimatic parameters of eco-physiological in Xuence derived from the current distribution of cork oaks. The climatic and edaphoclimatic parameters elaborated for two extreme WHC values (50 and 250 mm) are calculated for the whole study area and are mapped by means of a digital elevation model and a geographic information system. The results point to an important climatic potential area for high soil WHC values but there is also a remarkable dependence on this latter parameter, mainly in the Duero basin, since the limits of the climatic potential area are reduced strongly as WHC decreases. We deduce certain other conclusions as regards the importance of this variable in the potential distribution of species and in forestation and reforestation projects using this species.
Keywords: Cork oak; edaphoclimatic parameters; Potential distribution; Quercus suber; soil water holding capacity